2015
DOI: 10.1016/j.proeng.2015.08.556
|View full text |Cite
|
Sign up to set email alerts
|

MEMS-Based Terahertz Detectors

Abstract: A MEMS based novel THz detector structure is designed and realized by micro fabrication. The detector is then characterized to extract its mechanical performance. Operating in 1-5 THz band, the detector has a pixel size of 200 μm × 200 μm. Bimaterial suspension legs consist of Parylene-C and titanium, the pair of which provides a high mismatch in coefficients of thermal expansion. The pixel is a suspended Parylene-C structure having a 200 nm-thick titanium metallization. Operation principle relies on conversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Moreover, many studies reported numerous microelectro-mechanical-system (MEMS) based metamaterial and metasurface structures for numerous applications [18][19][20][21][22]. Ma et al [18] developed polarization-sensitive MEMS-based tunable metamaterials for the terahertz spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, many studies reported numerous microelectro-mechanical-system (MEMS) based metamaterial and metasurface structures for numerous applications [18][19][20][21][22]. Ma et al [18] developed polarization-sensitive MEMS-based tunable metamaterials for the terahertz spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…At 480 GHz, the system manifested a high contrast switching efficiency of 16.5 dB. Meanwhile, Bilgin et al [20] developed a MEMS-based THz detector which was characterized to extract its mechanical performance in 2015. The detector had a pixel size of 200 × 200 µm, working between 1 and 5 THz bands.…”
Section: Introductionmentioning
confidence: 99%